Maximization of economic benefits of fattening guinea pig through feed restriction - Meza, Elmer (2023)
The aim of this study was to evaluate the effect of the temporary restriction of balanced feed on the maximization of the economic benefits of fattening guinea pigs. In total, 100 male and female guinea pigs of the Red Line of 21 ± 3 days of age were used, distributed in 5 metallic cages of 4 levels and 5 animals per cage. The diets of feed restriction were: T1 (ad libitum), T2 (14 days + 50% ration), T3 (21 days + 50% ration), T4 (14 days + 25% ration) and T5 (21 days + 25% ration). The ad libitum ration consisted of 10 g/animal/day with increments of 4 g per week up to a maximum consumption of 66 g/animal/day. Green alfalfa was supplied in a proportion equivalent to 10% of body weight. By using body weights, weekly feed consumption and unit prices, growth functions (S), production (Q) and accumulated economic benefits (B) were established. The first partial derivative was applied to B to obtain profit maximization values (BMax), whose conjugation with Q and S, allowed estimating body weights (QMax) and maximum fattening times (SMax) of the experimental groups. The results showed a better compensatory response in male guinea pigs and a higher BMax in T4 compared to T1 (control), with the disadvantage of requiring higher SMax, but which is favourable for achieving higher QMax. It is concluded that a restriction level of 25% of the daily ration for 14 days is appropriate to maximize the economic benefits of male and female guinea pigs.